Are Orchids Left and Dandelions Right? Frontal Brain Activation Asymmetry and Its Sensitivity to Developmental Context. (August 2014) - Fortier, Paz; Van Lieshout, Ryan J.; Waxman, Jordana A.; Boyle, Michael H.; Saigal, Saroj; Schmidt, Louis A.
To clarify long-standing conceptual and empirical inconsistencies in models describing the relation between frontal brain asymmetry and emotion, we tested a theory of biological sensitivity to context. We examined whether asymmetry of alpha activation in frontal brain regions, as measured by resting electroencephalography, is sensitive to early developmental contexts. Specifically, we investigated whether frontal asymmetry moderates the association between birth weight and adult outcomes. Adults with left frontal asymmetry (LFA) who were born at extremely low birth weight exhibited high levels of attention problems and withdrawn behaviors in their 30s, whereas normal-birth-weight adults with LFA had low levels of these problem behaviors. Adults with right frontal asymmetry (RFA) displayed a relatively moderate amount of problem behavior regardless of birth weight. Our findings suggest that LFA is associated with sensitivity to developmental context and may help explain why LFA is associated with both positive and negative outcomes, whereas RFA seems to be associated with a more canalized process in some contexts.